Using the Analytical Network Process (ANP) based on BOCR Model to select the most suitable region for forestation with almond species - MARYAM FAZLOLLAHI MOHAMMADI; AKBAR NAJAFI; FATEMEH AHMADLO (Smujo International, 2015)
Abstract. Mohammadi MF, Najafi A, Ahmadlo F. 2015. Using the Analytical Network Process (ANP) based on BOCR Model to select the most suitable region for forestation with almond species. Nusantara Bioscience 7: 118-127. Forestation is the answer not only to the growing demand for timber and wood fiber, but also to the problem of deforestation. Forests in arid and semi-arid regions are in the specific conditions because of being in short of water and soil nutrition. Therefore, protection and rehabilitation of these forests is of very important due to its environmental condition as well as selecting suitable species for forestation. Considering all aspects of forestation in an effort to improve forest practices requires an approach that addresses multiple criteria and incorporates a wide range of data. After that, the approach should provide a framework to evaluate both quantitative and qualitative criteria. In this study, the Analytical Network Process (ANP) is utilized to evaluate four existing sites for forestation with Almond (Amygdalus scoparia) in Markazi province, central of Iran. The ANP framework helps forest managers to prioritize all the alternatives and criteria with respect to each other and developing their corresponding preferences. This study is an analysis of the environmental, social-economic, and sustainability-genetic diversion context of forestation with the goal of making forest practices more sustainable. The results indicate that Risk and Cost priorities are more important in making decision (0.53, 0.47), compared to Benefits and Opportunities (0.29, 0.25). The final synthesis of the system shows that Sarabadan (B site) is the best choice among four potential regions which were evaluated for forest plantation based on judgment’s comparisons.